Accelerating preliminary low-carbon design for products by integrating TRIZ and Extenics methods. (September 2017) - Ren, Shedong; Gui, Fangzhi; Zhao, Yanwei; Xie, Zhiwei; Hong, Huanhuan; Wang, Hongwei
Low-carbon performance as well as the quality and cost of a new product are normally emphasized in the early phase of low-carbon design for products. Although the TRIZ method and Extenics theory can be applied separately to solve contradiction problems in design field, these two methods have their weaknesses in applications. The purpose of this study is to provide a novel model for accelerating the preliminary low-carbon design by integrating the TRIZ and Extenics methods. Analysis tools and knowledge base tools of TRIZ are adopted to generate generic strategies; basic-element theory and dependent function of Extenics are used to qualitatively and quantitatively describe the conflict problem in a formalized model, and detailed transformation operations are employed to achieve the feasible design solutions. Innovative design schemes for two kinds of conflict problems of the screw air compressor demonstrate the effectiveness of the proposed method.